Simulating ecological and evolutionary systems in C - Wilson, Will (Cambridge University Press, 2000)
Using the programming language C, the book starts with elementary programs modeling stochastic birth-death processes, with programming complexity increasing as the chapters progress. Wilson covers all the important features of C: arrays, files, pointers, and structures, within biologically motivated simulations. Although computer simulations of extremely complicated biological processes are released from rigid mathematical constraints, he places each of the simulations in the context of a mathematical formulation examined either analytically or numerically.